2017
DOI: 10.29273/jkema.2017.1.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Activities of Tibialis Anterior, Peroneus Longus, and Tibialis Posterior Muscles according to Lunge Squats and Bulgarian Split Squats in a Healthy Population

Abstract: Background Previous studies reported that one-leg squat has various advantages in functional activities, no study has studied the effect of muscle activity on ankle stability. This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons. org/licenses/by-nc/4.0) which permits unrestricted noncommercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Purpose The purpose of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In cases of ankle instability, the ankle eversion muscle is weakened [9], and there is hip and lumbopelvic muscle weakening [12,32]. The tibialis anterior functions to prevent the foot from being dragged through the dorsiflexion while walking and to prevent the inversion, or plantar flexion, which is a posture that can lead to ankle sprain.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of ankle instability, the ankle eversion muscle is weakened [9], and there is hip and lumbopelvic muscle weakening [12,32]. The tibialis anterior functions to prevent the foot from being dragged through the dorsiflexion while walking and to prevent the inversion, or plantar flexion, which is a posture that can lead to ankle sprain.…”
Section: Discussionmentioning
confidence: 99%
“…The distance between the electrodes was 2 cm. For PL and PB, electrodes were attached distal to the fibular head at one-fourth and three-fourths of the fibular length [11,22].…”
Section: Surface Electromyographymentioning
confidence: 99%
“…Local muscle fatigue may have effects exercise performance and loading, causing the stress distribution on the musculoskeletal structure to change ( RADIN, 1986 ; Christina et al, 2001 ; Kellis and Liassou, 2009 ; Tiwari et al, 2021 ; Yahya et al, 2022 ). As a major player in ankle motion, the dorsiflexors use concentric contraction to increase dorsiflexion before landing in a lunge to provide adequate landing cushion range ( Kim et al, 2017 ). With a greater range of motion (ROM) in the ankle dorsiflexion, the body can take less impact when landing and be more cushioned.…”
Section: Introductionmentioning
confidence: 99%
“…During the landing phase of the lunge, the dorsiflexors alternate with the plantar flexors; although the plantar flexors are dominant, the dorsiflexors also have an irreplaceable role. It has been shown that when the knee is flexed beyond 90°, the plantar flexors’ eccentric contraction increases during lunge landing, but the dorsiflexors also increase their activity and contribute to ankle stability ( Lees and Hurley, 1994 ; Kim et al, 2017 ; Lee and Loh, 2019 ). Furthermore, the effect of dorsiflexor fatigue on ankle motion during landing is currently unknown.…”
Section: Introductionmentioning
confidence: 99%